Non-invasive vagus nerve stimulation improves clinical and molecular biomarkers of Parkinson’s disease in patients with freezing of gait - Banashree Mondal (Nature Portfolio, 2021)
Abstract Non-invasive vagus nerve stimulation (nVNS) is an established neurostimulation therapy used in the treatment of epilepsy, migraine and cluster headache. In this randomized, double-blind, sham-controlled crossover trial we explored the role of nVNS in the treatment of gait and other motor symptoms in Parkinson’s disease (PD) patients. In a subgroup of patients, we measured selected neurotrophin levels and markers of inflammation and oxidative stress in serum, before and after the experimental intervention. Thirty-three PD patients with associated freezing of gait were randomised to either nVNS or sham. After baseline assessments, patients were instructed to deliver 6 two-minute stimulations (total 12 min/day) of the nVNS/sham device (electroCore, Inc. USA) for one month at home. Patients were then re-assessed. After a washout period of one month, the same patients were allocated to the alternate treatment arm and the same process was followed. Significant improvements in key gait parameters were observed with nVNS, including walking speed, stance time and step length, compared to sham. Similarly, overall motor function (MDS-UPDRS III) also improved significantly following nVNS stimulation. Serum Tumor Necrosis Factor (TNF)-α and glutathione levels decreased and brain-derived neurotrophic factor (BDNF) levels increased significantly (p < 0.05) after treatment with nVNS. Here we present the first double-blind sham-controlled trial evidence of the efficacy and safety of nVNS in the treatment of gait and motor function in patients with PD.